Distinct Effects on Splicing of Two Monoclonal Antibodies Directed against the Amino-terminal Domain of Galectin-3 - Gray, Richard M. (2008)
Previous experiments had established that galectin-3 (Gal3) is a factor involved in cell-free splicing of pre-mRNA. Addition of monoclonal antibody NCL-GAL3, whose epitope maps to the NH(2)-terminal 14 amino acids of Gal3, to a splicing competent nuclear extract inhibited the splicing reaction. In contrast, monoclonal antibody anti-Mac-2, whose epitope maps to residues 48–100 containing multiple repeats of a 9-residue motif PGAYPGXXX, had no effect on splicing. Consistent with the notion that this region bearing the PGAYPGXXX repeats is sequestered through interaction with the splicing machinery and is inaccessible to the anti-Mac-2 antibody, a synthetic peptide containing three perfect repeats of the sequence PGAYPGQAP (27-mer) inhibited the splicing reaction, mimicking a dominant-negative mutant. Addition of a peptide corresponding to a scrambled sequence of the same composition (27mer-S) failed to yield the same effect. Finally, GST-hGal3(1–100), a fusion protein containing glutathione S-transferase and a portion of the Gal3 polypeptide including the PGAYPGXXX repeats, also exhibited a dominant negative effect on splicing.